On the role of anthropogenic climate change in the emerging food crisis in southern Africa in the 2019–2020 growing season. (12th March 2020) - Wolski, Piotr; Lobell, David; Stone, Dáithí; Pinto, Izidine; Crespo, Olivier; Johnston, Peter
Abstract : Anthropogenic climate change likely influences the beginning of 2020 growing season's water deficit in parts of southern Africa, with severe consequences to food security.